2014
DOI: 10.5603/piap.2014.0041
|View full text |Cite
|
Sign up to set email alerts
|

Application of Impulse Oscillometry in Respiratory System Evaluation in Elderly Patients

Abstract: As R5-R20 is regarded as a measure of peripheral airways resistance, IOS may serve as an interesting complementary or alternative method for spirometry in elderly subjects for evaluation of the state of respiratory system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 18 publications
(20 reference statements)
0
20
0
2
Order By: Relevance
“…COPD is characterized by the incomplete reversibility of airflow limitations; however, it is generally believed that FEV 1 is unable to fully evaluate pulmonary function, especially in cases of small airway dysfunction, while IOS can provide more detailed information on pulmonary function, especially on the assessment of peripheral airway conditions, which is the main location of COPD airflow limitation 3,13,14. In this study, FVC, FEV 1 , FEV 1 /FVC, and MMEF decreased in COPD patients compared with healthy controls, which reflected airflow limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COPD is characterized by the incomplete reversibility of airflow limitations; however, it is generally believed that FEV 1 is unable to fully evaluate pulmonary function, especially in cases of small airway dysfunction, while IOS can provide more detailed information on pulmonary function, especially on the assessment of peripheral airway conditions, which is the main location of COPD airflow limitation 3,13,14. In this study, FVC, FEV 1 , FEV 1 /FVC, and MMEF decreased in COPD patients compared with healthy controls, which reflected airflow limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, it is easy to produce false-positive results because of the change in bronchomotor tone caused by repeated forced breathing, especially in the elderly. Thus, studies concerning the quality of spirometry in elderly patients showed that only slightly >30% of patients were able to perform spirometry that fulfilled all the quality criteria as defined by European Respiratory Society/American Thoracic Society standards,3,4 and the proportion in the advanced elderly was even lower 5. Furthermore, FEV 1 cannot fully assess lung function, particularly the identification of small airway abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Because FOT does not require the forced expiratory maneuvers needed to generate spirometry data, it can be performed easily in pediatric patients3,4 and adults who are unable to perform spirometry 2,5. It has been reported that FOT measurements may be more sensitive than forced expiratory volume in 1 second (FEV 1 ) for measuring the effects of bronchodilator drugs in patients with COPD and asthma 68.…”
Section: Introductionmentioning
confidence: 99%
“…La oscilometría de impulso puede ser una alternativa a la espirometría y da información acerca de las propiedades de resistencia del sistema respiratorio. Esto se evaluó en un estudio que tomó 277 informes de oscilometría de impulso en pacientes entre 65 a 96 años y los comparó con la espirometría, para encontrar que las resistencias medidas con oscilometría de impulso (R5, R5-R20) y frecuencia de resonancia (Fres) se correlacionaron de manera significativa con el VEF 1 , considerando que la oscilometría de impulso puede servir como un método complementario o alternativo a la espirometría para la evaluación del estado del sistema respiratorio (1). No tiene ninguna contraindicación excepto aquellas alteraciones anatómicas que no permitan realizar una respiración o volumen corriente.…”
Section: Introductionunclassified
“…It has been used for early assessment of respiratory system impedance in asthma and chronic obstructive pulmonary disease, interstitial lung diseases, mechanical pulmonary changes in patients (1) Medicina Interna, Fellow de Neumología. Hospital Santa Clara.…”
mentioning
confidence: 99%